Innominate uteroumbilical ligament: a rare support of uterus - Singh, Kamal; Kumar, Piyush; Rohilla, Aarti; Katoch, Namrata; Kaur, Kamalpreet (International Journal of Research in Medical Sciences, 2018)
The ligaments along with the pelvic floor muscles are important supports of uterus and are supposed to help in maintaining the normal positioning of the uterus and prevent its prolapse. In present case report an unknown uteroumbilical ligament have been found extending from the uterus to the anterior abdominal wall of a female cadaver during the dissection. The ligament provides extra support to the uterus. It would have presumably helped in preventing uterine prolapse and retroversion of uterus. Such kind of structures around uterus and other pelvic organs when go unnoticed may complicate pregnancies and pose risk to life during surgeries. Thus, present case report will help in enhancing our knowledge related to gross anatomy as well as it will further enrich the literature data.